EL PROBLEMA DE LA ESCALA DE PLANCK - Monroy Cárdenas, Oscar (2009)
Searching Planck´s Regimen utilizing Planck´s Principle, Heisenberg´s uncertainly Principle and Einstein´s existence equation, it emerges concept of physical point which that would be a hole as extension of 10 -35 m through the Universe, so it would produce 10 -8 of materia/antimateria one a 10-43 s. It deduces that any physiscal entity could vibrate at frequencies larger to 10 43 Hz. Also it deduces, at Planck´s Regimen, that temperature would be about 3× 10 32 K order. Considerating pulsations at Planck´s Regimen of each physical structures, it deduces that Universe has dual character. It means that conception about of space, it would be actually a tridimensional surface of two faces.